What is the true in vitro potency of oxytetracycline for the pig pneumonia pathogens Actinobacillus pleuropneumoniae and Pasteurella multocida?. Issue 5 (18th January 2017) - Dorey, L.; Hobson, S.; Lees, P.
Abstract : The pharmacodynamics of oxytetracycline was determined for pig respiratory tract pathogens, Actinobacillus pleuropneumoniae and Pasteurella multocida . Indices of potency were determined for the following: (i) two matrices, broth and pig serum; (ii) five overlapping sets of twofold dilutions; and (iii) a high strength starting culture. For A. pleuropneumoniae, minimum inhibitory concentration (MIC) was similar for the two matrices, but for P. multocida, differences were marked and significantly different. MIC and minimum bactericidal concentration (MBC) serum: broth ratios for A. pleuropneumoniae were 0.83:1 and 1.22:1, respectively, and corresponding values for P. multocida were 22.0:1 and 7.34:1. For mutant prevention concentration (MPC) serum: broth ratios were 0.79:1 ( A. pleuropneumoniae ) and 20.9:1 ( P. multocida ). These ratios were corrected for serum protein binding to yield fraction unbound (fu) serum: broth MIC ratios of 0.24:1 ( A. pleuropneumoniae ) and 6.30:1 ( P. multocida ). Corresponding fu serum: broth ratios for MPC were almost identical, 0.23:1 and 6.08:1. These corrections for protein binding did not account for potency differences between serum and broth for either species; based on fu serum MICs, potency in serum was approximately fourfold greater than predicted for A. pleuropneumoniae and sixfold smaller than predicted for P. multocida . For both broth and serum and both bacterial species, MICs were also dependent on initial inoculum strength. The killing action of oxytetracycline had the characteristics of codependency for both A. pleuropneumoniae and P. multocida in both growth media. The in vitro potency of oxytetracycline in pig serum is likely to be closer to the in vivo plasma/serum concentration required for efficacy than potency estimated in broths.